COMPARISON OF AS, HG AND TL HIGH-FREQUENCY ELECTRODELESS LAMPS FOR DETECTION OF ENVIRONMENTAL POLLUTION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Nowadays, there is an increasing necessity to determine the concentration of different substances in the environment in low concentrations, as more and more attention is paid to environmental pollution. This work is devoted to the comparison of main characteristics of high-frequency electrodeless light sources with different fillings for their use in high precision atomic absorption analysers.The spectral line intensities and profiles were studied in special design light sources, manufactured at Institute of Atomic Physics and Spectroscopy, with arsenic, mercury and thallium filling. Special attention is devoted to the UV lines of 193.7 nm and 197.2 nm of As, 276.8 nm, 377.6 nm of Tl and 253.7 nm of Hg spectral lines. The intensities and profiles were measured by means of a Fourier transform spectrometer.The deconvolution procedure was implemented to obtain the real form of emitted profiles for further analysis, since in the case of low –pressure or cold plasma, the instrumental function is on the same order that experimental profile and it has to be taken into account. The instrumental function can distort the real spectral line shape significantly, for example, it changes the width of the spectral line that leads to the uncertainties in the determination of such important plasma parameters like temperature. The instrumental function can conceal a detailed structure of the spectral line, like the dip in the line center caused by the self-absorption (self-reversal) and characterizing the radiation trapping.The integrated areas, values of self-absorption, and other parameters were obtained and compared for all fillings as a function of working regimes.